Say good-bye - Anderson, Laurie Halse (Vet volunteers, 2008)
Seeing Jane's dog, Yum-Yum, help cheer up children in a cancer ward makes Zoe think about having her puppy, Sneakers, trained to do therapy, too, especially when Yum-Yum becomes very ill.